2011
DOI: 10.2478/s11756-011-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic responses of cellular metabolites in Escherichia coli to pulse addition of substrates

Abstract: Abstract:We conducted an integrated study of cell growth parameters, product formation, and the dynamics of intracellular metabolite concentrations using Escherichia coli with genes knocked out in the glycolytic and oxidative pentose phosphate pathway (PPP) for glucose catabolism. We investigated the same characteristics in the wild-type strain, using acetate or pyruvate as the sole carbon source. Dramatic effects on growth parameters and extracellular and intracellular metabolite concentrations were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We also examined whether alternative substrates for FbiD could be used to remove the reliance on PEP, showing that although 3PG is a viable substrate and is more abundant in E. coli, the use of the P. rhizoxinica FbiD did not result in higher 3PG-F 420 yields (compared with F 420 ), presumably because of the downstream enzymes, which are sourced from M. smegmatis , have a preference for F 420 -metabolites over 3PG-F 420 metabolites. Replacing other enzymes in the pathway with those from P. rhizoxinica may be a worthwhile strategy to improve 3PG-F 420 yield, as the theoretical yield of 3PG-F 420 is similar to that of PEP-derived F 420 and strategies have already been developed to improve 3PG availability by increasing glycolytic flux by knocking out the zwf gene involved in first step of pentose phosphate pathway 55 . Other strategies that we tested to increase F 420 yield included increasing PEP production through over expression of PPS; this produced the highest productivity with pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined whether alternative substrates for FbiD could be used to remove the reliance on PEP, showing that although 3PG is a viable substrate and is more abundant in E. coli, the use of the P. rhizoxinica FbiD did not result in higher 3PG-F 420 yields (compared with F 420 ), presumably because of the downstream enzymes, which are sourced from M. smegmatis , have a preference for F 420 -metabolites over 3PG-F 420 metabolites. Replacing other enzymes in the pathway with those from P. rhizoxinica may be a worthwhile strategy to improve 3PG-F 420 yield, as the theoretical yield of 3PG-F 420 is similar to that of PEP-derived F 420 and strategies have already been developed to improve 3PG availability by increasing glycolytic flux by knocking out the zwf gene involved in first step of pentose phosphate pathway 55 . Other strategies that we tested to increase F 420 yield included increasing PEP production through over expression of PPS; this produced the highest productivity with pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…The pgi gene is the second enzyme of the glycolytic pathway and can promote G6P catabolism in the glycolytic pathway and the subsequent TCA cycle instead of the PPP . Therefore, we chose to additionally prevent glucose-6-phosphate (G6P) catabolism through the glycolytic pathway by deleting the gene pgi , which encodes the G6P isomerase.…”
Section: Resultsmentioning
confidence: 99%
“…The pgi gene is the second enzyme of the glycolytic pathway and can promote G6P catabolism in the glycolytic pathway and the subsequent TCA cycle instead of the PPP. 35 Therefore, we chose to additionally prevent glucose-6-phosphate (G6P) catabolism through the glycolytic pathway by deleting the gene pgi, which encodes the G6P isomerase. As expected, when we engineered a Δpgi strain in the E. coli BL21(DE3) ΔxylB background, we found that strain GX6 performed better than GX1, producing more xylose.…”
Section: Analysis Of Energy Metabolites Proved That the Glycolytic Pa...mentioning
confidence: 99%